2008
DOI: 10.1088/1468-6996/9/4/044201
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in compensated and uncompensated semiconductors

Abstract: We investigate the localization and superconductivity in heavily doped semiconductors. The crossover from the superconductivity in the host band to that in the impurity band is described on the basis of the disordered three-dimensional attractive Hubbard model for binary alloys. The microscopic inhomogeneity and the thermal superconducting fluctuation are taken into account using the self-consistent 1-loop order theory. The superconductor-insulator transition accompanies the crossover from the host band to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…3. We have calculated the correlation function of SC order parameter and found that the long range correlation of the superconductivity is suppressed as increasing the impurity potential for U imp 45:5 [21]. According to these results, we obtain the schematic figure for the phase diagram in Fig.…”
Section: Phase Diagrammentioning
confidence: 88%
See 3 more Smart Citations
“…3. We have calculated the correlation function of SC order parameter and found that the long range correlation of the superconductivity is suppressed as increasing the impurity potential for U imp 45:5 [21]. According to these results, we obtain the schematic figure for the phase diagram in Fig.…”
Section: Phase Diagrammentioning
confidence: 88%
“…The SC correlation develops in the ''dirty region'' which includes many impurities while the SC correlation is suppressed in the ''clean region'' [21]. This spatial dependence is opposite to that in high-T c cuprates [22].…”
Section: Sc Fluctuation Around Sitmentioning
confidence: 90%
See 2 more Smart Citations
“…Theoretically, the superconductivity in doped semiconductors can be interpreted in terms of degree of randomness caused by the impurity band, which is related to E A [17,18,42]. When E A is large (acceptor level is deep), the randomness caused by the impurity band is large.…”
Section: Discussionmentioning
confidence: 99%